Studi Tentang Kualitas Pelayanan Ojek Online (Ojol) Grabbike dan Pengaruhnya Terhadap Kepuasan Pelanggan di Kota Tegal - Faridah, Yayat Hidayat Amir, Basukiyatno (Universitas PGRI Madiun, 2020)
The study aims to determine the quality of Grabbike online motorcycle taxi service and its effect on customer satisfaction in the Tegal City area. The quantitative approach is used as a source of data processing so that the results are presented. The study population was GrabBike online motorcycle taxi (OJOL) customers in Tegal City for one week, 1000 customers. This research used incidental sampling technique in sampling. Determination of the number of samples using the Slovin formula. From the total population of 1000 obtained a sample of 100 customers as respondents. Data collection uses observation methods, questionnaires, and documentation. The research instrument was in the form of observation sheets and questionnaires with 22 items of statements that had been tested for validity and reliability. Datalysis was analyzed with linear regression. The results showed that the quality of service had a positive and significant effect on GrabBike online motorcycle taxi customer satisfaction as evidenced by the results of the calculation of a simple linear regression analysis of Y = 16.078 + 0.520X, with the significance of the variable service quality was 0,000 because the significance value of 0,000 <0.05 was concluded service quality has a significant effect on customer satisfaction variables on OJOL GrabBike in Tegal City, meaning Ha is accepted while H0 is rejected.